Epidemiology and risk factors for infections in myelodysplastic syndromes. Issue 6 (9th September 2013) - Sullivan, L.R.; Sekeres, M.A.; Shrestha, N.K.; Maciejewski, J.P.; Tiu, R.V.; Butler, R.; Mossad, S.B.
Abstract We conducted a case–control study to describe the epidemiology and risk factors for infections requiring hospitalization in patients with myelodysplastic syndromes (MDS). Of 497 patients identified, 103 patients developed 201 episodes of infection. The probability of acquiring an infection 1 year from date of MDS diagnosis was 15% (95% confidence interval [CI] 12–18%). Patients developing infections had decreased survival compared to those who did not (P = 0.007). Significant risk factors for infection were higher risk MDS (hazard ratio [HR] = 2.7, 95% CI = 1.7–4.1, P < 0.0001), nadir absolute neutrophil count <500/mL (HR = 1.8, 95% CI = 1.2–2.7, P < 0.007), chronic obstructive pulmonary disease (HR = 2.6, 95% CI = 1.4–4.9, P < 0.003), history of other malignancy (HR 2.0, 95% CI = 1.3–3.1, P < 0.003), and autoimmune disease (HR 2.9, 95% CI = 1.4–6.0, P < 0.005). Age, nadir platelet count <20, 000/mL, diabetes mellitus, and MDS treatment were not significant risk factors. Pneumonia was the most common infection, and bacteria the predominant pathogens.